Evidence for lineage continuity between early serous proliferations (ESPs) in the Fallopian tube and disseminated high‐grade serous carcinomas. Issue 3 (27th September 2018) - Soong, Thing Rinda; Howitt, Brooke E; Miron, Alexander; Horowitz, Neil S; Campbell, Frank; Feltmate, Colleen M; Muto, Michael G; Berkowitz, Ross S; Nucci, Marisa R; Xian, Wa; Crum, Christopher P
Abstract: The distal Fallopian tube is a site of origin for many 'ovarian' high‐grade serous carcinomas (HGSCs) with intraepithelial carcinomas (STICs) that share identical TP53 mutations with metastatic tumors. TP53 mutation‐positive early serous proliferations (ESPs) comprise a spectrum including p53 signatures and serous tubal intraepithelial lesions (STILs) and are not considered malignant; however, ESPs are often the only abnormality found in Fallopian tubes of women with metastatic HGSC. The purpose of this study was to determine if a relationship exists between isolated ESPs and concurrent metastatic HGSCs in the absence of STIC. Fallopian tubes from 32 HGSCs without a co‐existing STIC/HGSC in the endosalpinx were exhaustively sectioned. The presence of either STIC/HGSC or ESP in the endosalpinx was documented and DNA from tissues containing ESPs, concurrent HGSC, and control epithelia were interrogated for TP53 mutations by targeted amplicon‐based sequencing with average coverage reads >4000 across DNA replicate samples. Serial sectioning revealed a previously unrecognized STIC/HGSC in 3 of 32 (9.3%) and ESPs in 13 (40.6%). Twelve contained TP53 mutations. Nine (75%) shared identical TP53 mutations with concurrent HGSCs, four at high (≥ 5%) and five at low (< 5%) allele frequency. All control epithelia were TP53 mutation‐negative. This study, for the first time, indicates lineage identity between ESPs in the distal tube and some metastatic HGSCs via a shared site‐specific TP53 mutation. It supports a novel serous carcinogenic sequence in which an ESP could eventually culminate in a metastatic serous cancer via 'precursor escape' and would explain the apparent sudden onset of cancers without co‐existing STICs. This paradigm for serous cancer development underscores the likelihood that multiple precursor types in the Fallopian tube contribute to serous cancer development with implications for the evolution, pathologic classification, and prevention of this lethal malignancy. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.